2015
DOI: 10.1111/efp.12205
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Alnus glutinosa susceptibility to Phytophthora ×alni infection and its geographic pattern in the Czech Republic

Abstract: Summary Variation in natural susceptibility of the black alder population to Phytophthora ×alni (PA), the oomycete pathogen causing a devastating disease of alder, and its possible relationship to geographic origin, was studied in vitro using branch inoculation tests. Ninety black alder genotypes from different regions of the Czech Republic and two isolates of PA were employed. Host susceptibility varied significantly. After 1 week of infection, the lesion surface areas ranged from 254 to 2051 mm2 and from 19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…There are several examples of differences in susceptibility to pathogens among tree host individuals and populations from different locations (Roll‐Hansen, ; Hunt et al ., ; Carnegie et al ., ; Swedjemark et al ., ; Hamilton et al ., ; Balmelli et al ., ; Romeralo et al ., ; Štochlová et al ., ). For example, European larch ( Larix decidua ) differs strongly in susceptibility to larch canker ( Lachnellula willkommii ) depending on the provenance (Yde‐Andersen, ).…”
Section: Evolutionary Aspects Of Ash Genetic Diversity and Variation mentioning
confidence: 97%
“…There are several examples of differences in susceptibility to pathogens among tree host individuals and populations from different locations (Roll‐Hansen, ; Hunt et al ., ; Carnegie et al ., ; Swedjemark et al ., ; Hamilton et al ., ; Balmelli et al ., ; Romeralo et al ., ; Štochlová et al ., ). For example, European larch ( Larix decidua ) differs strongly in susceptibility to larch canker ( Lachnellula willkommii ) depending on the provenance (Yde‐Andersen, ).…”
Section: Evolutionary Aspects Of Ash Genetic Diversity and Variation mentioning
confidence: 97%
“…The results of infection of alder with P. alni complex depend on several factors: type of inoculated organ [40,41], method of inoculation [40], environment condition [42], derivation of isolate-host genotype, geographic provenience [37], and, as was shown in our study, from what source the isolates were obtained-diseased trunks or soil from under these trees.…”
Section: Discussionmentioning
confidence: 55%
“…Jung et al [34] indicate the necessity of planting alder genotypes of higher resistance to P. alni root rot. Štochlová et al [37] studied the susceptibility of 90 black alder genotypes from different Czech regions against two isolates of P. × alni, observing infections on cut fragments of branches and recorded the area of necrotic lesions on phloem parts. A great variability between genotypes and isolates was observed in that experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison to results from other studies suggests a higher aggressiveness of the PAA and PAU isolates or higher susceptibility of the A. glutinosa genotypes used in our study. Isolate genotype seems to be an important factor affecting lesion development and mortality, as demonstrated by various experiments with PAA (Haque and Diez, 2012;Chandelier et al, 2016;Štochlová et al, 2016;Zamora-Ballesteros et al, 2017). The host plant susceptibility or resistance depends on many variables.…”
Section: Discussionmentioning
confidence: 98%
“…The host plant susceptibility or resistance depends on many variables. Significant differences in susceptibility/tolerance of individual A. glutinosa trees to PAA were demonstrated in Belgium, Germany and the Czech Republic (Jung and Blaschke, 2006;Chandelier et al, 2016;Štochlová et al, 2016). In an extensive study including 90 genotypes of A. glutinosa sampled across the Czech Republic Štochlová et al (2016) found that differences in susceptibility to PAA were also depending on the geographic origin and altitude of the alder genotypes.…”
Section: Discussionmentioning
confidence: 99%